Mapping the leap: differences in quality improvement in relation to assessment rating outcomes - Davis, Belinda; Dunn, Rosemary; Harrison, Linda J.; Waniganayake, Manjula; Hadley, Fay; Andrews, Rebecca; Li, Hui; Irvine, Susan; Barblett, Lennie; Hatzigianni, Maria (Frontiers in Education, 2023)
Introduction Australia’s National Quality Standard (NQS) outlines the criteria to assess the quality of early childhood services. A four-point rating scale: (i) Exceeding NQS; (ii) Meeting NQS; (iii) Working Toward NQS; and (iv) Significant Improvement Required is applied to services following a regular assessment and rating process. Settings rated as Working Toward are reassessed within 12 months. Most settings achieved a one-step improvement in this Time 2 reassessment, moving to a Meeting rating but some settings made a two-step improvement, moving to an Exceeding rating. The QIP is a key document used by authorities to assess the quality of a service. Methods A grounded theory, data driven approach was taken to deepen understanding of quality rating improvements in long day care services in Australia of quality rating improvements by early childhood education and care [ECEC] services in Australia. This study, part of the second phase of a three phase study involved a document analysis of the Time 2 Quality Improvement Plans (QIPs) of a representative sample of Long Day Care (LDC) services (n = 60) from all Australian states and territories to determine what factors may have contributed to these different levels of improvement, with a focus on Quality Area 1 (QA1) (Educational programs and practices) and Quality Area 7 (QA7) (Governance and leadership). The study utilized the semantic analysis tool Leximancer 4.5. Leximancer 4.5 statistically analyses the semantic relationships between concepts in documents by measuring word proximity and correlation. The software creates visual maps of concepts and their connections to each other in texts. Concepts located near one another on the map are more likely to be contextually related. This tool is particularly useful when there are multiple, complex documents to analyze, reducing the potential biases that can arise from documents that use language with which these researchers are very familiar with. Results The analysis found clear differences between the Time 2 QIPs of services who had made a two-step rating improvement and those who made a one-step improvement. Two-step (Exceeding NQS) category improvers for QA1 placed attention in their QIPs on improvement to the program and overall practice, with an orientation to the role of the educational leader. Two-step (Exceeding NQS) category improvers for QA7 seemed to be more oriented to a systemic view of the processes encompassed by QA7; how the management of the service and information supports the work of educators, with stronger links made between leadership roles (the manager and nominated supervisor) and the work of educators. Discussion The QIPs demonstrated how the intentional and systemic processes in these quality areas related to practice, management, and leadership.